Stabilization in a two dimensional two-species aerotaxis-Navier–Stokes system. (February 2021) - Jeong, Eunji; Kim, Junha; Lee, Jihoon
Abstract: This paper deals with the two-species aerotaxis-Navier–Stokes equations with Lotka–Volterra competitive kinetics in a two dimensional domain Ω ⊂ R 2 . We consider the general chemotactic sensitivity functions and oxygen(chemical) consumption rate functions. We obtain the stabilization of the solution to the system. For the specific conditions on the chemotactic sensitivity and initial data, we obtain the global stabilization when the competition between two species is stronger than that of each own species.